High-performance double-null plasmas under radiating mantle scenarios on DIII-D. (May 2019) - Petrie, T.W.; Grierson, B.; Osborne, T.H.; Turco, F.; Allen, S.L.; Fenstermacher, M.E.; Ferron, J.R.; Guo, H.Y.; Hinson, E.; La Haye, R.; Lasnier, C.J.; Leonard, A.W.; et al.
Highlights: The location for EC heating plays a major role in impurity transport. Impurity seeding makes high β plasmas very susceptible to confinement-killing MHD. Access to regimes of improved τE predicted by ELITE was supported experimentally. Abstract: Actively enhancing plasma radiated power has been used to reduce divertor heat flux in high power, high-performance double null divertor (DND) and near-DND plasmas in DIII-D, while at the same time maintaining acceptable energy confinement. One form of this approach that we focus on here is the radiating mantle. The effectiveness of the radiating mantle was found to depend strongly on the location of electron cyclotron (EC) heating deposition and on the effect that seed impurities have on triggering inimical MHD activity inside the plasma. In addition, we present experimental support for the predictions made by the ELITE boundary stability code (Snyder et al., 2002, [1]) for ways to improve confinement and fueling in these high-performance plasmas. Representative AT operating conditions were H98  ≈ 1.4–1.7, βN  ≈ 3–4, and q95  ≈ 4.7–6.5.